Conditional ablation of vasopressin‐synthesizing neurons in transgenic rats. (8th November 2021) - Watanabe, Jun; Takayanagi, Yuki; Yoshida, Masahide; Hattori, Tatsuya; Saito, Michiko; Kohno, Kenji; Kobayashi, Eiji; Onaka, Tatsushi
Abstract: Vasopressin‐synthesizing neurons are located in several brain regions, including the hypothalamic paraventricular nucleus (PVN), supraoptic nucleus (SON) and suprachiasmatic nucleus (SCN). Vasopressin has been shown to have various functions in the brain, including social recognition memory, stress responses, emotional behaviors and circadian rhythms. The precise physiological functions of vasopressin‐synthesizing neurons in specific brain regions remain to be clarified. Conditional ablation of local vasopressin‐synthesizing neurons may be a useful tool for investigation of the functions of vasopressin neurons in the regions. In the present study, we characterized a transgenic rat line that expresses a mutated human diphtheria toxin receptor under control of the vasopressin gene promoter. Under a condition of salt loading, which activates the vasopressin gene in the hypothalamic PVN and SON, transgenic rats were i.c.v. injected with diphtheria toxin. Intracerebroventricular administration of diphtheria toxin after salt loading depleted vasopressin‐immunoreactive cells in the hypothalamic PVN and SON, but not in the SCN. The number of oxytocin‐immunoreactive cells in the hypothalamus was not significantly changed. The rats that received i.c.v. diphtheria toxin after salt loading showed polydipsia and polyuria, which were rescued by peripheral administration of 1‐deamino‐8‐d ‐arginine vasopressin via an osmotic mini‐pump. Intrahypothalamic administration of diphtheria toxin in transgenic rats under a normal hydration condition reduced the number of vasopressin‐immunoreactive neurons, but not the number of oxytocin‐immunoreactive neurons. The transgenic rat model can be used for selective ablation of vasopressin‐synthesizing neurons and may be useful for clarifying roles of vasopressin neurons at least in the hypothalamic PVN and SON in the rat. Abstract : We characterized a transgenic rat line that expresses a mutated human diphtheria toxin receptor under control of the vasopressin gene promoter. Intracerebroventricular administration of diphtheria toxin under a hyperosmotic condition induced selective ablation of vasopressin neurons in the hypothalamic paraventricular nucleus (PVN) and the supraoptic nucleus (SON) but not in the suprachiasmatic nucleus. Intrahypothalamic administration of diphtheria toxin induced selective ablation of vasopressin neurons in the injected areas of the PVN and SON.